Dual-energy X-ray absorptiometry is a reliable non-invasive technique for determining whole body composition of chickens. (6th March 2019) - Schallier, S; Li, C; Lesuisse, J; Janssens, G P J; Everaert, N; Buyse, J
ABSTRACT: In this study, a Lunar Prodigy dual-energy X-ray absorptiometry (DEXA ) scanner was validated as a technique to estimate chicken body composition in a non-invasive way. Former research has emphasized the importance of validation of every scanner and software version. In a first trial, DEXA estimated body composition for broilers was correlated with chemical carcass analysis to develop prediction equations. As such, those equations can be used in later experiments with chickens to correct DEXA estimations to estimate body composition accurately by DEXA. DEXA estimated fat mass, lean tissue mass, bone mineral content (BMC ) and total body mass, which is the sum of fat, lean mass and BMC, were compared to chemically analyzed crude fat, lean mass as the sum of protein and water and body ash content and scale body weight, respectively. Those regression equations were then used in a second trial to determine body composition based upon DEXA for breeders at different ages. In this experiment, fat and lean tissue determined by DEXA, were compared to dissection parameters commonly used for assessing carcass quality, namely breast muscle and abdominal fat. The first trial showed that DEXA provides high correlations for body mass (ρ = 1) and the individual tissue masses separately (ρ ranging between 0.98 and 1). These high correlations allow for accurate prediction of those components with the developed regression equations. Proportional fat and lean tissue were correlated with their chemical counterparts, however, to a lower extent than absolute values due to lower variation between the proportional weights. BMC percentage was not significantly correlated with ash percentage. Furthermore, in trial 2 high correlations were observed between dissection parameters and DEXA-corrected estimations. These correlations show that DEXA can assess carcass quality in breeders without sacrificing the birds. In conclusion, DEXA is a reliable technique to estimate breeder and broiler body composition in a non-invasive way, hence allowing for longitudinal studies over longer periods of time while avoiding sacrificing of birds.